DEVELOPMENT OF WAQF WITH A SHEEP FARMING MODEL (CASE STUDY OF MITRA TANI FARM) - Dil Piero, Lulu Musa; Arsyanti, Laily Dwi; Setiawan, Budi Susilo (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
The management of waqf funds doesn’t have to be used for buildings or as vacant land only but can be used as a productive activity. One of them is through the Sheep Farming Productive Waqf program. It’s because sheep's needs are categorized into the community's basic needs. The purpose of this study was to analyze the sheep farm waqf management by MT Farm and the community's perception of the waqf of sheep farm. The development of the livestock waqf program is carried out through the Business Model Canvas approach, which is tested using the SEM Lisrel method. Some of the research methods used include interviews and questionnaire collection. A total of 170 respondents were successfully collected and processed using the overall match test of the variable model, the match test of the measurement model of all variables, and the general match test of the structural equation model. The results of this study shows the standardization value less than ≥1.96 makes several indicators insignificant, including customer relationship indicators, value propositions, channels, and critical resources. This means that public education on sheep farming waqf must continue to be provided so that the livestock waqf management program at MT Farm can be feasible to continue to be developed. In addition, it can help increase the supply of sheep livestock from the land, livestock and operational waqf components simultaneously.